2016
DOI: 10.1007/s00590-016-1775-x
|View full text |Cite
|
Sign up to set email alerts
|

Complete excision of the infrapatellar fat pad is associated with patellar tendon shortening after primary total knee arthroplasty

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Studies favouring preservation of the IPFP during TKA cite an increased risk of scarring and therefore shortening of the patellar tendon caused by disruptions of the anastomotic links that exist in the IPFP [8]. The resulting shortening of the patellar tendon is then thought to contribute to increased stiffness of the knee, patella baja and altered kinematics [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies favouring preservation of the IPFP during TKA cite an increased risk of scarring and therefore shortening of the patellar tendon caused by disruptions of the anastomotic links that exist in the IPFP [8]. The resulting shortening of the patellar tendon is then thought to contribute to increased stiffness of the knee, patella baja and altered kinematics [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, both patellar tendon shortening and joint line elevation can result in patella baja (PB) [ 2 , 3 ]. PB may cause anterior knee pain [ 3 – 6 ], limited range of motion (ROM) [ 3 , 7 ], joint stiffness [ 8 , 9 ], and prosthetic impact and abrasion [ 9 , 10 ]. PB is divided into true PB (TPB) and pseudo-PB (PPB).…”
Section: Introductionmentioning
confidence: 99%
“…Patellar tendon shortening could be one of the reasons for post-TKA anterior knee pain as findings from Gwyn et al ’s retrospective study7 reported that complete IPFP resection was associated with patellar tendon shortening 1 year after TKA. The authors had noted that studies also reporting IPFP excision during TKA did not alter the patellar tendon length 8 9.…”
mentioning
confidence: 98%